Sentinels in Saltator atricollis (Passeriformes: Emberizidae) - RAGUSA-NETTO,J. (2001)
I studied the existence of sentinels in Saltator atricollis in a 'campo-cerrado' (Brazilian savanna) during the breeding seasons of 1994-95 and 1995-96. Groups of this species consisted of two to seven birds (N = 25). Sentinels were present (mean ± sd) 62% ± 9% of the time, and most sentinel bouts lasted from less than one to six minutes (although in some occasions for more than 30 min.). Overlap of two or more sentinels occurred on average only 3.2% of the time with birds on guard. Sentinels commonly gave contact calls in the beginning and/or at the end of a sentinel bout. The group size had no effect on time with sentinels. However the encounter rate between raptors and groups significantly influenced the time guarded. The results of this study suggests that the ability of sentinels to detect predators may play a central role as an anti-predator device.